Encapsulation of bone marrow-MSCs in PRP-derived fibrin microbeads and preliminary evaluation in a volumetric muscle loss injury rat model: modular muscle tissue engineering - Özge Lalegül-Ülker; Şükran Şeker; Ayşe Eser Elçin; Yaşar Murat Elçin (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Repair of volumetric muscle loss (VML) injuries is a complicated endeavour which necessitates the collaborative use of different regenerative approaches and technologies. Herein is proposed the development of fibrin-based microbeads (FMs) alone or as a bone marrow mesenchymal stem cell (MSC) encapsulation matrix for modular muscle engineering. FMs were generated through the ionotropic gelation of alginate and fibrinogen obtained from the platelet-rich plasma of whole blood, and then removing the alginate by citrate treatment. FMs were first characterized by FT-IR, SEM and water uptake tests. Then, the stability of FMs and the mitochondrial dehydrogenase activity of the MSCs encapsulated in FMs were evaluated under in vitro culture conditions. Eventually, the regenerative capacity of the cell-devoid and MSCs-encapsulated FMs was evaluated in a rat VML injury model involving 8 × 4×4 mm3-size bilateral defects in the biceps femoris muscles. The histochemical, immunohistochemical and semi-quantitative histomorphological scoring results retrieved at 30, 60 and 180 days demonstrated that the cell-devoid FMs supported muscle regeneration to a great extent. Moreover, MSCs-encapsulated FMs were more effective in shortening the regeneration period of the injured tissue of the rat VML, resulting in good myofibre orientation, while the Sham group resulted in incomplete repair with fibrotic scar tissue formations.